2002
DOI: 10.1029/2001wr000404
|View full text |Cite
|
Sign up to set email alerts
|

Tidal meanders

Abstract: .[1] Observational evidence is presented on the geometry of meandering tidal channels evolved within coastal wetlands characterized by different tidal, hydrodynamic, topographic, vegetational and ecological features. New insight is provided on the geometrical properties of tidal meanders, with possible dynamic implications on their evolution. In particular, it is shown that large spatial gradients of leading flow rates induce important spatial variabilities of meander wavelengths and widths, while their ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
213
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(231 citation statements)
references
References 27 publications
15
213
3
Order By: Relevance
“…Marani et al (2002) fi tted Equation (1) to seven tidal channels, and noted that the value of L b varied in a highly site-specifi c manner, while the ratio of L b to the channel length tended to be larger in short channels than in long channels. Woodroffe and Mulrennan (1993, p 106) considered the changes in the width profi les of estuarine channels in the Mary River plains during the Holocene, and found that the convergence lengths of palaeochannels and modern channels were reasonably similar despite huge differences in channel size.…”
Section: Introductionmentioning
confidence: 99%
“…Marani et al (2002) fi tted Equation (1) to seven tidal channels, and noted that the value of L b varied in a highly site-specifi c manner, while the ratio of L b to the channel length tended to be larger in short channels than in long channels. Woodroffe and Mulrennan (1993, p 106) considered the changes in the width profi les of estuarine channels in the Mary River plains during the Holocene, and found that the convergence lengths of palaeochannels and modern channels were reasonably similar despite huge differences in channel size.…”
Section: Introductionmentioning
confidence: 99%
“…These intertwined processes hinder the tendency of the system to develop a self-organized configuration [Rinaldo et al, 1999b]. Tidal channels are also highly sinuous, with meanders that are geometrically similar to the meanders developing in rivers [Marani et al, 2002]. However, the bidirectionality of the discharge in tidal channels often implies a meander evolution that departs from terrestrial meanders [Fagherazzi et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…Intertidal marsh surface water hydrology is characterized by tidal flood and ebb in the channel network [Fagherazzi et al, 1999;Marani et al, 2002Marani et al, , 2003. During especially high tides, the channels fill beyond bankfull capacity and tidal waters flood across the marsh plain, influenced by vegetation roughness [Temmerman et al, 2005;van Proosdij et al, 2006].…”
Section: Introductionmentioning
confidence: 99%